Effect of KRAS mutation status on clinicopathological characteristics and overall survival in patients with rectal cancer - Shengbin Zheng; Zhijie You; Guodon Guo; Zhijing Lin; Siming Wang; Guohua Yang (BMC Gastroenterology)
Abstract Background KRAS mutations in rectal cancer are associated with a conflict prognosis. This study aimed to compare clinicopathological outcomes of patients and tumor criteria between wKRAS and mKRAS, as well as overall survival in the two groups. Methods The research retrospectively analyzed a cohort of 193 patients who received surgical treatment for rectal adenocarcinoma between May 2015 and December 2023. The patients were categorized into two groups according to their KRAS status: wild-type KRAS (wKRAS) and mutant KRAS (mKRAS), with performing research on mKRAS G12D and mKRAS G13D mutation. Results The mKRAS group included 100 patients(51.8%) and had no significantly difference in age, sex, distance from anus, tumor node metastasis(TNM), lymphovascular invasion(LVI), grade differentiation, and perineural invasion(PNI), carcinoembryonic antigen(CEA) level than that in wKRAS group.KRASG12D group had significantly more poorer differentiation(9/34,26.5% vs. 10/93,10.7%,p = 0.046), PNI(24/34,70.6%vs.42/93,45.2%,p = 0.016) and higher TD(8/34,23.5% vs.8/93,8.6%,p = 0.035) respectively, p < 0.05. Compared with the wKRAS group, the mean OS of mKRAS group was worse(58.07 m vs.57.55 m), but had no significant difference(p = 0.0866). In comparison to the wKRAS group, the overall survival duration was notably reduced in the KRASG12D group (p = 0.0482), whereas no significant difference was observed in the KRASG13D group (p = 0.1848). Additionally, a COX survival analysis was conducted, revealing that KRASG12D, along with higher TNM stage, LVI, tumor deposits, and PNI, were all associated with a decrease in survival time for patients with rectal cancer; however, these factors did not reach statistical significance (p > 0.05). Conclusion The overall survival duration for wKRAS was superior to that of mKRAS; however, the difference between the two groups was not statistically significant. In contrast, the survival time for KRASG12D was significantly poorer than that for wKRAS, while no such difference was observed for KRASG13D. Retrospectively registered K2024-07-037.2024,7.